Nutrition culture in English Premier League football: a bourdieusian analysis - Foo, W. L.; Tester, E.; Close, G. L.; Cronin, C. J.; Morton, J. P. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: In 2020, the Union of European Football Associations (UEFA) published evidence based nutritional guidelines for elite football (1), reflecting the growing recognition of the role of nutrition in supporting football performance. In practice, however, players do not readily meet these guidelines (2). While behaviour change models have explored enablers and barriers to nutritional adherence (3), the cultural factors influencing players` nutritional habits also warrant investigation. Through the lens of Bourdieu Theory (4), this study aimed to explore players` perceptions of the nutrition culture within the professional football environment. METHODS: An interpretivist paradigm, which emphasizes that reality is subjective and socially constructed, underpins this study. Accordingly, face-to-face semi structured interviews were conducted with purposively sampled male footballers from the English Premier League (EPL) (5 British, 5 Migrant; mean age: 26 ± 6; mean EPL appearances: 106 ± 129). Questions were open-ended to maximise contribution. Data were abductively analysed using thematic analysis (5). Bourdieu theory which includes habitus (acquired disposition and behaviour), capitals (economic, e.g. resources; social, e.g. status), field (arena of social practice) and doxa (taken-for-granted beliefs) informed interviews and analysis RESULTS: This study revealed five key themes: (1) Habitus, shaped by familial, ethnic and religious backgrounds, influences footballers` dietary habits; (2) Via social capital, managers, teammates and online influences, significantly impact footballers` dietary practices; (3) The rise of football clubs` and players` economic capitals spurred advancements in nutrition provision; (4) An unequal distribution of economic capitals has led to hierarchical practice in the performance nutrition field with personalized nutrition being somewhat enacted at the higher levels, and (5) Body composition measurement is a `doxic` practice in professional football that warrants challenge. CONCLUSION: Data showed that the habitual nutritional practices of professional players is influenced by cultural factors associated with their personal upbringing and the context of the specific club in question (e.g. economic resources and/or social capital exerted by managers). Additionally, the field of performance nutrition within professional football is influenced by stakeholder doxic beliefs surrounding the perceived optimal body composition of players, where managers also exert social capital. Practically, these data clearly demonstrate the necessity for player and stakeholder education programmes that seek to equip individuals with both knowledge and practical skillsets to ensure the successful translation of science to practice.